2010
DOI: 10.1111/j.1540-8167.2010.01919.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Endothelial Function in Patients with Atrial Fibrillation through Maintenance of Sinus Rhythm by Successful Catheter Ablation

Abstract: AF subjects have significantly impaired FMD, which can be reversed through maintenance of SR by successful CA. FMD(baseline), hs-CRP, and LAV are important predictors for AF recurrence after CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 34 publications
3
42
0
1
Order By: Relevance
“…The univariate and multivariate analyses found that LA diameter and a PM for AVB were associated with recurrence of AF. This finding also supports the results of previous studies [23][24][25] showing that the LA size is a well-known predictor of recurrence of AF after catheter ablation. Several mechanisms may account for the relationship between a PM for AVB and recurrence of AF.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The univariate and multivariate analyses found that LA diameter and a PM for AVB were associated with recurrence of AF. This finding also supports the results of previous studies [23][24][25] showing that the LA size is a well-known predictor of recurrence of AF after catheter ablation. Several mechanisms may account for the relationship between a PM for AVB and recurrence of AF.…”
Section: Discussionsupporting
confidence: 82%
“…29) Atrial dilatation is a predictor of recurrence of AF after catheter ablation. [23][24][25] However, because the slow idioventricular rhythm is prevented effectively by PM therapy in these patients, the effect of AVB on recurrence of AF need further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shin et al reported that catheter ablation for AF patients with no recurrence improved endothelial dysfunction by the measurement of flow-mediated dilation (FMD), but they needed for 6 months to the FMD score of control subject. 51 Furthermore, the patients with recurrence continue endothelial dysfunction after AF ablation. 51 However, some reports showed that HMG-CoA reductase inhibitors and omega-3 fatty acids had protective effectives for AF patients post-cardioversion or ablation.…”
Section: Discussionmentioning
confidence: 99%
“…51 Furthermore, the patients with recurrence continue endothelial dysfunction after AF ablation. 51 However, some reports showed that HMG-CoA reductase inhibitors and omega-3 fatty acids had protective effectives for AF patients post-cardioversion or ablation. 52, 53 We thought that the animal model without AF we used in this study is similar to that of patients post-cardioversion or ablation, and some continuous anticoagulant therapies or treatment for endothelial dysfunction might be beneficial in these patients without an AF condition.…”
Section: Discussionmentioning
confidence: 99%